Fight or Flight? Understanding Different Stakeholder Responses to Conservation Conflicts. Issue 6 (3rd June 2022) - Hodgson, Isla D.; Fischer, Anke; Redpath, Steve M.; Young, Juliette C.
Abstract: Efforts to manage conservation conflicts are typically focused on reconciling disputes between opposing stakeholders over conservation objectives. However, this is an oversimplification of conflict dynamics, driven by the difficulties of understanding and addressing deeper-rooted issues. In this study, an ethnographic approach using a combination of informal discussions, participant observation, and in-depth interviews was used to examine local stakeholder narratives around a conservation conflict over grouse shooting and raptor conservation. Analysis highlighted three main narratives – cooperation, resistance, and despondence, that served as a basis for individuals to justify their responses to conflict: to work toward collaboration, act antagonistically, or avoid. Our analysis suggests that the current status quo in conflict management serves to reinforce antagonistic positions. We recommend a more nuanced approach to understanding stakeholder decision-making that goes beyond superficial disputes to recognize diversity within stakeholder groups, access hidden voices, and encompass the wider socio-political context.